Agrio et Emulsio – development of new products with vinegar and sweetpotatoes - Basto De Lima, Maria Gabriela (2020)
Agrio et Emulsio project (POCI-01-0145-FEDER-023583) develops in vinegar and food emulsions areas. In line Agrio, vinegar technological ability enables the development of multiple products, by fermentative and non-fermentative prototyping. Articulating technological, laboratory and sensory tests and inspired both by the marinades in wine or vinegar of the Mediterranean gastronomy and in the traditional Portuguese recipe of “drunk” pear in red wine, two prototypes are undergoing final development, using sweet potato cultivars (Ipomoea batatas) as main ingredient. A sweet and sour “drunk” pickle has been developed by fresh pack pickling technology (without fermentation), using a spicy red wine vinegar with cinnamon and black pepper, sweetened with brown sugar and added Gin. The marinade was designed to be a ready-to-eat vegan product, with tofu and sweet potato previously salted in brine and then submerged in the marinade liquid. The marinade matrix is a diluted blend of red wine vinegar and regional liqueur wine from Ribatejo, flavored with red pepper, herbs and spices. Pre-salting in brine, maturation and the final heat treatment are fundamental for the quality and safety of both prototypes that were designed to provide innovation and convenience: new products with long shelf life, aims the preservation of seasonal/surplus raw materials.